41st Annual North American Meeting of the Society for Medical Decision Making; October 21, 2019; Portland, Oregon. Keynote Address: The More Who Die, the Less We Care. Issue 9 (September 2020) - Slovic, Paul
Abstract : (Abstracted from MDM Policy Pract 2020;5(1):2381468320914310. doi: 10.1177/2381468320914310) Dr Slovic, a psychologist at the University of Oregon, has devoted his research career to this topic. He is a member of the National Academy of Arts and Sciences.